2018
DOI: 10.1155/2018/4827353
|View full text |Cite
|
Sign up to set email alerts
|

Association between Prior Chlamydia trachomatis Infection and Ectopic Pregnancy at a Tertiary Care Hospital in South Western Uganda

Abstract: Background Increase in the number of ectopic pregnancy is attributed to increase in the incidence of pelvic infections. Chlamydia trachomatis is responsible for most of the sexually transmitted bacterial infections. If undetected and untreated, the infection can ascend to the upper genital tract and cause pelvic inflammatory disease (PID) and related sequelae (ectopic pregnancy and tubal factor infertility). Objective To determine the association between prior Chlamydia trachomatis infection and ectopic pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
3
1
Order By: Relevance
“…The current study showed that anti-Chlamydia immunoglobulin mean (IgG and IgM) were significantly higher among women with ectopic pregnancy in comparison to women with normal pregnancy. This relationship is similar to results of many studies such Abdullah study in Iraq [24] and Mpiima study in Uganda which revealed a significant positivity of IgG and IgM antibodies for Chlamydia Trachomatis among ectopic pregnancy group compare to women with normal pregnancy [25]. Also, a study carried out in Nigeria by Agholor [26] on 90 women with ectopic pregnancy and 98 women with normal pregnancy; they found that chlamydial infection has a limited effect in the pathogenesis of ectopic pregnancy with elevation of serum IgG and IgM antibodies for Chlamydia among women with ectopic pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…The current study showed that anti-Chlamydia immunoglobulin mean (IgG and IgM) were significantly higher among women with ectopic pregnancy in comparison to women with normal pregnancy. This relationship is similar to results of many studies such Abdullah study in Iraq [24] and Mpiima study in Uganda which revealed a significant positivity of IgG and IgM antibodies for Chlamydia Trachomatis among ectopic pregnancy group compare to women with normal pregnancy [25]. Also, a study carried out in Nigeria by Agholor [26] on 90 women with ectopic pregnancy and 98 women with normal pregnancy; they found that chlamydial infection has a limited effect in the pathogenesis of ectopic pregnancy with elevation of serum IgG and IgM antibodies for Chlamydia among women with ectopic pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…Although we reported a higher prevalence of chlamydia antibodies in our participants compared to others from the region, a study conducted in Uganda reported double our figures, where 60% of women with EP and 26.32% of those with an intrauterine pregnancy had chlamydia antibodies [ 17 ]. This may be attributed to differences in the prevalence of chlamydia in the general population.…”
Section: Discussioncontrasting
confidence: 64%
“…The minimal sample size was estimated using OpenEPI [ 16 ] based on the difference in the proportion of outcome (EP) according to parity (1 vs. >3) as reported by Mpiima et al [ 17 ] The authors reported the prevalence of ectopic pregnancy among those in parity of 1 (unexposed) to be 2.38% as opposed to those with parity >3 (exposed) which was 18.75%. A minimum sample size of 66 was required in each group to give the study 80% power at α = 0.05 (two-sided).…”
Section: Methodsmentioning
confidence: 99%
“…The result is in line with study result in France, 58 Brazil, 59 Cameroon, 60 and Uganda. 61 The above association could be explained by the infection, may ascend to the endometrium, and is responsible for the etiology of endometritis and salpingitis, and causes for ectopic pregnancy. 62 Moreover, the sexually transmitted infection may cause pelvic inflammatory disease and may lead to tubal dysfunction and aberrant implantation, which in turn promote the occurrences of ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%